Biohardening of Banana cv. Karpooravalli (ABB; Pisang Awak) With Bacillus velezensis YEBBR6 Promotes Plant Growth and Reprograms the Innate Immune Response Against Fusarium oxysporum f.sp. cubense - Saravanan, R.; Nakkeeran, S.; Saranya, N.; Kavino, M.; Ragapriya, V.; Varanavasiappan, S.; Raveendran, M.; Krishnamoorthy, A. S.; Malathy, V. G.; Haripriya, S. (Frontiers in Sustainable Food Systems, 2022)
Fungicides play an immense role in quenching the infection of panama wilt of banana. However, the use of fungicides and monoculture of banana cultivars have resulted in the development of new races like Race 4 which challenges scientists across the globe to identify new candidates for biological suppression of Fusarium oxysporum f.sp. cubense (Foc). Hence, attempts were made to dissect the endophytes from resistant banana cultivar YKM5 (Yengambi – AAA) to suppress Foc KP (Race 4) infecting Karpooravalli (ABB; Pisang Awak). Among the various endophytes, Bacillus velezensis YEBBR6 inhibited the mycelial growth up to 63% over control and hyper parasitized the mycelium of Foc KP. Scanning electron microscopic analysis revealed the ramification by B. velezensis over the hyphae of Foc KP leading to lysis. Analysis of VOCs/NVOCs compounds from the zone of inhibition, confirmed the presence of unique biomolecules including linoelaedic acid, nonanol, acetylvaleryl, 5 – hydroxyl methyl furfural, clindamycin, allobarbital, 3-thiazolidine carboxamide, azulene, aminomorpholine, procyclidine, campholic acid, 3 amino-4 hydroxy phenyl sulfone, 3 –deoxy mannoic lactone, hexadecanoic acid, oleic acid and dihydroacridine of antifungal cum antimicrobial nature. Considering the diverse antimicrobial property, biohardening of micropropagated banana cv. Karpooravalli (ABB) with liquid formulation of B. velezensis YEBBR6 (8×108 cfu/ml) and challenge inoculation with Foc KP promoted plant growth up to 100.42 percent compared to uninoculated control. Besides, incidence of Fusarium wilt was reduced by 100% over inoculated control. Further, the expression of defense genes WRKY, MAPK, CERK 1, LOX and PAL were increased by several folds compared to inoculated and healthy control and thus, suppressed Fusarium wilt of banana cv. Karpooravalli (ABB). Furthermore, cytoscape analysis of defense genes indicated the coordinated expression of various other genes associated with it. Hence, our study confirmed the scope for exploring B. velezensis on a commercial scale for the management of Fusarium wilt Race 4 causing wilt - across genomes of banana. Key words: Bacillus velezensis, Fusarium wilt, VOCs/NVOCs compounds, Biohardening, WRKY, MAPK, CERK 1, LOX, PAL, Fusarium oxysporum f.sp. cubense (Foc) race 4, Bacillus velezensis YEBBR6, , VOCs/NVOCs, defense gene expression bacterial endophytes biomolecules , disease suppression, anti-fungal activity, Bacillus velezensis , VOCS.